The impact of herbal incense on improving stress and memory impairment induced by repeated social defeat stress model in female mice - Minh Thai Nguyen; Ngoc Phuc Nguyen; Ngoc To Quyen Nguyen; Ngoc Phuc Nguyen Nguyen; Le Minh Hien Nguyen; Thanh Binh Nguyen; Huynh Nhu Mai (Pharmacia)
Nowadays, stress is becoming increasingly common, especially among those who experience violence and face an increased risk of developing mood disorders. As the need to find effective treatments for anxiety and depression is increasing, the use of herbal medicine is receiving more attention due to its perceived safety and therapeutic benefits. In this study, a social defeat model was developed using female mice to evaluate the anxiety-reducing and memory-improving effects of herbal incense containing agarwood (Aquilaria crassna), cinnamon (Cinnamomum cassia), and star anise (Illicium verum). A socially defeated state was induced on female mice by 10-day exposure to aggressive male mice. Female mice were then treated with herbal incense for 10 days. The treatment groups showed improved time spent in the interaction zone (social interaction test) and open arms (elevated plus maze test) as well as a percentage of novel object recognition, yet a decrease in immobility time (forced swim test). Additionally, treated mice showed reduced plasma corticosterone. These results indicated that herbal incense showed protective effects against stress and memory reduction. This study suggests that herbal incense containing agarwood, cinnamon, and star anise may offer an effective way to treat anxiety-related disorders. Further research is needed to pinpoint the active compounds and understand the mechanisms behind these therapeutic effects.